FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN ODHA DALAM MENJALANI TERAPI ANTIRETROVIRAL (ARV) PADA LAKI SEKS LELAKI (LSL) DI YAYASAN KANTI SEHATI SEJATI KOTA JAMBI 2025 - Dyah Ayu Nur Azizah; Adelina Fitri; Muhammad Syukri; Hendra Dhermawan Sitanggang (STKIP Subang, 2026)
Adherence to antiretroviral (ARV) therapy is an important factor in achieving successful HIV treatment. This study aimed to determine the factors associated with ARV therapy adherence among people living with HIV/AIDS (PLWHA) in the Men Who Have Sex with Men (MSM) group at Yayasan Kanti Sehati Sejati, Jambi City, in 2025. This study employed a cross-sectional design involving 150 respondents. Data were collected using questionnaires and health service records. Data were analyzed using the Chi-Square test. The results showed significant associations between age and ARV therapy adherence (p=0.000), social support (p=0.004), history of comorbidities (p=0.012), and duration of ARV therapy (p=0.014). Meanwhile, no significant associations were found between educational level, knowledge of ARV treatment, and ARV side effects and therapy adherence. Most respondents had a moderate level of adherence to ARV therapy. In conclusion, age, social support, history of comorbidities, and duration of therapy were associated with ARV therapy adherence among PLWHA in the MSM group. Efforts to improve adherence should focus on strengthening social support, continuous assistance, and monitoring of ARV therapy.